The Effectiveness of TikTok as an Online Learning Platform for Islamic Education - Jaza, Fandi Khusnul; Makrufi, Anisa Dwi (Sekolah Tinggi Ilmu Tarbiyah (STIT) Muhammadiyah Bangil in collaboration with Letiges & Association of Muslim Community in ASEAN (AMCA), 2025)
Digital technology has transformed how individuals acquire information, including in religious education. TikTok, one of the most popular social media platforms, is increasingly used as a medium for Islamic Religious Education (PAI). This study aims to analyze the effectiveness of TikTok in enhancing students’ understanding and application of Islamic values during online learning, with a specific focus on content delivered by Ustaz Irfan Rizki Haas. In this context, Although not officially mandated by schools, TikTok functions as a supplementary resource, utilized by teachers and accessed independently by students as part of their online Islamic religious education, Ustaz Irfan Rizki Haas, a well-known digital preacher with over 2.4 million followers. His unique approach to digital da'wah, characterized by engaging storytelling, emotional delivery, and contextual relevance, positions him as a central figure in this study. A descriptive quantitative method was employed, involving an online survey of 100 junior and senior high school students in Indonesia who actively engage with religious content on TikTok, particularly from Ustaz Irfan. The results indicate that 88% of respondents felt more motivated to learn about Islam, 87% reported an improvement in applying Islamic values in daily life, and 85% found themselves better able to distinguish between valid and misleading religious information. While TikTok demonstrates considerable potential as an innovative medium for Islamic learning, concerns remain regarding content credibility. Therefore, the involvement of educators and religious scholars is essential to guide students in critically engaging with accurate religious information. This study highlights TikTok’s role not only as a digital da'wah medium but also as a strategic tool in modern Islamic education, with Ustaz Irfan Rizki Haas serving as an influential role model. Future research is encouraged to explore the long-term impact of TikTok on Islamic religious education among students and to develop systematic content moderation strategies to ensure the quality and integrity of educational content delivered through the platform.